Avaliação de aminoácidos como palatabilizantes hídricos para gatos - Lizia Cordeiro de Carvalho (2018)
Two experiments were carried out to evaluate palatability; the coefficient of apparent digestibility of nutrients; fecal and urinary characteristics; haematological parameters and serum concentrations of urea and creatinine for adult cats. In experiment 1, the palatability and waterconsumption test was performed, which evaluated the inclusion of 0.5% of L-proline, L-ornithine or L-cysteine in water. The first choice, first consumption and total consumption of water with amino acid compared to the control water were evaluated. Experiment 2 consisted of thedigestibility test and fecal quality evaluation, urinary parameters, blood count and serum concentrations of urea and creatinine in cats consuming water with the inclusion of 0.5% Lproline. Cats showed no preference for water containing amino acids. Among the amino acids,the water containing L-cysteine was the one with the lowest intake at the first consumption. The same was observed for consumption. In the second experiment the inclusion of L-proline in the water did not alter the feed consumption, its digestibility and the fecal quality of the animals. The water consumption was the same among the treatments, not modifying also in the urinary parameters. For the blood evaluations, there was no significant difference between treatments. All parameters were within the physiological limits for the species, except for the parameters of monocytes, eosinophils and urea, which were higher than those recommended. The addition of amino acids at the concentration studied was not sufficient to increase water consumption. However, the added water of 0.5% L-proline did not influence diet digestibility, urinaryparameters and blood parameters evaluated.